The Clique Covering Number for the Strong Product of Generalized Cycles - Badalyan, Sevak H. (Mathematical Problems of Computer Science, 2021)
In this paper the clique covering number for the strong product of generalized cycles is investigated. A method is given to construct a minimal clique cover in case some conditions hold.